PENGARUH AKUNTABILITAS, INDEPENDENSI, DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA BATAM - Yuliana; Natalia , Erni Yanti (LPPM Universitas Putera Batam, 2025)
In the era of globalization and increasingly fierce business competition, transparency and accuracy of financial reports are the key to business sustainability. Reliable financial reports help investors, creditors and governments in making strategic decisions. Audits play an important role in ensuring that reports can be trusted and comply with applicable accounting standards, thereby supporting economic stability and growth. This research was conducted with the aim of examining the influence of auditor accountability, independence and professionalism on audit quality at Public Accounting Firms in Batam City. This research uses a quantitative approach by collecting primary data through distributing questionnaires carried out using the Google Form platform as well as a direct approach to respondents. Sampling in this study used a quota sampling technique which was determined by the researcher as many as 50 respondents. The results obtained from the partial t test show that accountability has no effect on audit quality, independence has no effect on audit quality, and professionalism has an effect on audit quality. Furthermore, it is known from the results of the simultaneous F test that simultaneously accountability, independence and auditor professionalism have a significant influence on audit quality.